RELASI GENDER DALAM SEMIOTIKA SASTRA ARAB: PERSPEKTIF SEMIOTIKA ROLAND BARTHES - Abd Syukur Abu Bakar; Muhammad Rusydi (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2022)
This article focuses on revealing how gender ralation are recorded in the semiotics of Arabic literature through Roland Barthes' semiotics as its perspective. Roland Barthes is a thinker who has great attention to the study of semiotics, including in this context, by seeing a text as a sign system. The constructive relationship that is built between the sign, the signifier, and the signified as described by Roland Barthes in his semiotic thinking requires the reader to be active in dialectic with writers who write literary works so that the denotative meaning of an Arabic literary work can metamorphose into a connotative meaning. In its practical framework, Arabic literary works in various forms such as poetry, prose, and others are full of depictions of women and their social roles that must be approached with semiotic studies so that moral messages are found oriented to gender equality for men and women. In this process, a reader should not be fixated on the denotative meaning of a literary text that is very full of ethical and aesthetic values, but what must be done is that the reader must be active in transforming the denotative meaning into a connotative meaning that continues to have a dialectic with the surrounding cultural context or with the context culture of writers.